PENGARUH MODEL DISCOVERY LEARNING PADA HASIL BELAJAR BIOLOGI SISWA KELAS X1 SMA BUDI UTOMO - Eka Lokaria; Harmoko Harmoko; Putri Lestari (Jurnal Perspektif Pendidikan, 2021)
One of the learning models that emphasizes learning activities related to the environment around studens is the doscovery learning model which is able to help and improve each studen’s ability to solve problems streng then self concept, encourage each studen to be more active in seeking information and knowledge. This study aims to determine the effecy of the discovery learning model on biologi students at SMA Budi Utomo. The study was conducted in two classes X1.A (control) and X1.B (Experiment) The results of the post-test data analysis using the t-test, obtained a t-value of 2.97. This result is compared with the ttable value at a significant level of 5%, which is 1.68. This shows that the value of tcount (2,97) > ttable (1,68). So it can be concluded that there is an influence of the Discovery Learning learning model on the learning outcomes of Class XI students at SMA Budi Utomo.